Credit risk modeling and valuation: An introduction - Kay Giesecke (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
Credit risk refers to the risk of incurring losses due to unexpected changes in the credit quality of a counterparty or issuer. In this paper we give an introduction to the modeling of credit risks and the valuation of credit-risky securities. We consider individual as well as correlated credit risks.
urn:nbn:de:kobv:11-10049126
Keywords: G12; G13; 330; compensator; intensity; credit risk; default risk; structural approach; reduced form approach